Komentarz do dekretu Trybunału Roty Nuncjatury Apostolskiej w Hiszpanii c. Morán Bustos z dnia 26 marca 2007 r. zarządzający przyjęcie sprawy o orzeczenie nieważności małżeństwa do zwyczajnego postępowania w II instancji - Białobrzeski, Tomasz (Ius Matrimoniale, 2015)
Presented decree of the Tribunal of the Rota of the Apostolic Nunciature in Spain was based on the can 1682 § 2 CCL and article 265 § 5 of Dignitas Connubii. The justices in this decree refer to the case about the nullity of the marriage due to ordinary examination in a new grade of trial (article 265 § 1 Dignitas Connubii). Presented document shows the very thorough treatment of the case on the just starting appeal. In comprehensive way, according to norm of laws the reasons that were expressed briefly and indicated that further instruction were required (article 265 § 5 Dignitas Connubii). In addition it contains part in iure, in which the judge refers to the title from which the case was carried on in the I instance, i.e. to lack of discretion of judgment (no inner freedom) as to essential marital rights and obligations.